Lou Engle & Dean Briggs, Puasa Yesus, Nafiri Gabriel, Jakarta, 2016. : Lou Engle & Dean Briggs, Jesus Fast, Nafiri Gabriel, Jakarta, 2016. - Victor Christianto (Sekolah Tinggi Teologi Satyabhakti, Malang)
In spiritual formation or discipline, one area that many of Christ's mature disciples often overlook is fasting. Especially fasting over a long period of time. This book written by Lou Engle and Dean Briggs reminds us to focus more on the area.%MCEPASTEBIN% === Dalam formasi atau disiplin spiritual, salah satu area yang kerap terabaikan oleh banyak murid Kristus dewasa ini adalah berpuasa. Terutama berpuasa dalam jangka waktu panjang. Buku yang ditulis Lou Engle dan Dean Briggs ini mengingatkan kita untuk lebih bertekun di area tersebut.